EVALUATION OF GINGER (ZINGIBER OFFICINALE ROSC.) GENOTYPES UNDER COCONUT ECOSYSTEM - K. S. SANGEETHA; S. SUBRAMANIAN (The Bioscan, 2015)
An experiment was conducted to evaluate the performance of thirty ginger genotypes under coconut ecosystem at the Coconut Nursery, Horticultural College and Research Institute, Tamil Nadu Agricultural University, Coimbatore during the period from 2012 to 2013. The results showed the supremacy of the genotype Z0 26 over the other genotypes, as ZO 26 showed increment in plant height (60.0 cm), number of tillers / plant (9.8), number of leaves / plant (148.56) and leaf area (2378.72 cm 2 ) respectively at 150 DAP and per plant fresh yield (179.42 g), per plot yield (3.22 kg/1.13 m 2 ) and estimated yield per hectare (28.62 t ha -1 ) at 240 DAP. Dry recovery percentage was maximum (25.16%) in the genotype ZO 12. On the basis of good performance ZO 26 is adjudged as the suitable ginger genotype under coconut shade condition.